Acceptance, safety and complications of postpartum intra uterine contraceptive device: a prospective study in tertiary care hospital - Jain, Rekha; Sharma, Manisha; Gupta, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrauterine contraceptive device is a long acting, effective and reversible method of contraception. It can be inserted post placental during vaginal or LSCS delivery and within 48 hours of delivery. This study evaluates the acceptance, safety, side effects and complications associated with immediate post-partum intrauterine contraceptive device (PPIUCD) insertion. Methods: The study was conducted at Hindu Rao Hospital and NDMC Medical College, Delhi for a period of 18 months. Patients admitted and delivered at Hindu Rao Hospital were counseled for PPIUCD, CuT 380 A / CuT 375 insertions and it was inserted within 10 minutes of delivery of placenta during vaginal delivery or LSCS or within 48 hours of delivery. Patients were followed at 6 weeks and then between 6 to 12 months of delivery for continuation, side effects or any complications. Results: After counseling 1253 (9.8%) patients agreed for PPIUCD insertion out of which 650 patients came for follow up. 46% women came for routine follow up while 54.06% came with one or the other complications. Missed thread was most common complications, followed by bleeding P/V and pain abdomen. Expulsion in 5.5% and CuT failure was seen in 0.92% women only. Removal of IUCD was done in 94 patients for one or other reasons. There was retention of PPIUCD in 84.5% while removal was done in 14.5% during period of 6 months to one year follow up. Missed thread was main cause of anxiety among acceptors. Conclusions: Immediate PPIUCD is safe and effective method of contraception with a high retention rate. Though acceptance in initial months was less but it gradually increased over time with increasing awareness, counseling of patients and training of health personnel.